Leukocytes Differentiation of Goldfish (Carassius auratus) Infected with Aeromonas hydrophila Bacteria and Post-treatment with Propolis Solution - M Riswan; Iesje Lukistyowati; Henni Syawal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2021)
This study aims to determine the best dose of propolis to treat Carassius auratus infected with Aeromonas hydrophila seen leucocyte differentiation from C.auratus. The method used was experimental method with Completely Randomized Design (CDR) with one factor consisting of five treatment levels and three replications. The treatment was Kn (not infected with A. hydrophila and untreated propolis), Kp (infected with A. hydrophila but not treated with propolis), and fish infected with A. hydrophila treated propolis with dose P1 (700 ppm), P2 (800 ppm), and P3 (900 ppm). Treatment is done by injection of propolis in fish infected by A. hydrophila in intramuscular. The fish used are 8-10 cm in size and kept for 14 days post-infection. The results showed that propolis solution has been able to treat C. auratus from infected A. hydrophila. The dose of propolis 800 ppm is the best dose to treat C. auratus infected A.hydrophila, seen from leukocyte differentiation (lymphocyte 80,25%, monocytes 10,09% and neutrophils 9,66%).